Investigating wound healing characteristics of gingival and skin keratinocytes in organotypic cultures. (October 2022) - Smith, Chris J.; Parkinson, Eric K.; Yang, Jingjuin; Pratten, Jonathan; O'Toole, Edel A.; Caley, Matthew P.; Braun, Kristin M.
Highlights: Gingival junctional epithelium is recapitulated using a novel 3D organotypic method. Gingival models re-epithelialize faster than skin in the 2D and 3D environment. Gingival and skin models undergo different forms of migration. Several genes related to wound healing are upregulated in gingiva compared to skin. PITX1 could play role in superior oral wound healing. Abstract: Objectives: The gingiva heals at an accelerated rate with reduced scarring when compared to skin. Potential well-studied factors include immune cell number, angiogenesis disparities and fibroblast gene expression. Differential keratinocyte gene expression, however, remains relatively understudied. This study explored the contrasting healing efficiencies of gingival and skin keratinocytes, alongside their differential gene expression patterns. Methods: 3D organotypic culture models of human gingiva and skin were developed using temporarily immortalised primary keratinocytes. Models were wounded for visualisation of re-epithelialisation and analysis of keratinocyte migration to close the wound gap. Concurrently, differentially expressed genes between primary gingival and skin keratinocytes were identified, validated, and functionally assessed. Results: Characterisation of the 3D cultures of gingiva and skin showed differentiation markers that recapitulated organisation of the corresponding in vivo tissue. Upon wounding, gingival models displayed a significantly higher efficiency in re-epithelialisation and stratification versus skin, repopulating the wound gap within 24 hours. This difference was likely due to distinct patterns of migration, with gingival cells demonstrating a form of sheet migration, in contrast to skin, where the leading edge was typically 1-2 cells thick. A candidate approach was used to identify several genes that were differentially expressed between gingival and skin keratinocytes. Knockdown of PITX1 resulted in reduced migration capacity of gingival cells. Conclusion: Gingival keratinocytes retain in vivo superior wound healing capabilities in in vitro 2D and 3D environments. Intrinsic gene expression differences could result in gingival cells being 'primed' for healing and play a role in faster wound resolution. Clinical Significance Statement: The successful development of organotypic models, that recapitulate re-epithelialisation, will underpin further studies to analyse the oral response to wound stimuli, and potential therapeutic interventions, in an in vitro environment.